Investigating motor initiation and inhibition deficits in patients with Parkinson's disease and freezing of gait using a virtual reality paradigm. (19th November 2016) - Georgiades, Matthew J.; Gilat, Moran; Ehgoetz Martens, Kaylena A.; Walton, Courtney C.; Bissett, Patrick G.; Shine, James M.; Lewis, Simon J.G.
Highlights: Impaired motor initiation and inhibition is common with freezing of gait in PD. These impairments are explored with a virtual reality task. Freezers experienced slower footstep initiation and more frequent start hesitation. Freezers took longer to execute motor inhibition with increased frequency of stop failures. Cues requiring additional cognitive processing exacerbated stopping impairments. Abstract: Freezing of gait (FOG) is a common, disabling symptom of Parkinson's disease (PD) that is associated with deficits in motor initiation and inhibition. Understanding of underlying neurobiological mechanisms has been limited by difficulties in eliciting and objectively characterizing such gait phenomena in the clinical setting. However, recent work suggests that virtual reality (VR) techniques might offer the potential to study motor control. This study utilized a VR paradigm to explore deficits in motor initiation and stopping performance, including stop failure in PD patients with (Freezers, 31) and without (Non-Freezers, 23) FOG, and healthy age-matched Controls (15). The VR task required subjects to respond to a series of start and stop cues while navigating a corridor using ankle flexion/extension movements on foot pedals. We found that Freezers experienced slower motor output initiation and more frequent start hesitations (SHs) (initiations greater than twice a subject's usual initiation latency) compared to Non-Freezers and Controls. Freezers also showed more marked inhibitory impairments, taking significantly longer to execute motor inhibition, and experiencing an increased frequency of failed stopping in response to stop cues compared to Non-Freezers and Controls. Stopping impairments were exacerbated by stop cues requiring additional cognitive processing. These results suggest that PD patients with FOG have marked impairments in motor initiation and inhibition that are not prominent in patients without FOG, nor healthy controls. Future work combining such VR paradigms with neuroimaging techniques and intra-operative deep brain recordings may increase our understanding of these phenomena, promoting the development of novel technologies and therapeutic approaches.